2021
DOI: 10.3390/su13147873
|View full text |Cite
|
Sign up to set email alerts
|

Blood, Hair and Feces as an Indicator of Environmental Exposure of Sheep, Cow and Buffalo to Cobalt: A Health Risk Perspectives

Abstract: Exposure to toxic metals (TMs) such as cobalt (Co) can cause lifelong carcinogenic disorders and mutagenic outcomes. TMs enter ground water and rivers from human activity, anthropogenic contamination, and the ecological environment. The present study was conducted to evaluate the influence of sewage water irrigation on cobalt (Co) toxicity and bioaccumulation in a soil-plant environment and to assess the health risk of grazing livestock via forage consumption. Cobalt is a very necessary element for the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
4
2
Order By: Relevance
“…The highest concentration of Cu and Cd was reported in wheat and rice in most of the studies on soil receiving a high load of sewage sludge or wastewater 36 . Ni in sampled wheat grains irrigated through the Hudiara drain of the current study was higher than the permissible limits of FAO and WHO 2000 37 . The higher content of Ni in wheat grain might be due to different inputs of waste from different industries, especially glass, paint, and textile 38 .…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The highest concentration of Cu and Cd was reported in wheat and rice in most of the studies on soil receiving a high load of sewage sludge or wastewater 36 . Ni in sampled wheat grains irrigated through the Hudiara drain of the current study was higher than the permissible limits of FAO and WHO 2000 37 . The higher content of Ni in wheat grain might be due to different inputs of waste from different industries, especially glass, paint, and textile 38 .…”
Section: Discussioncontrasting
confidence: 60%
“…The higher metal level in meat could be due to the grazing of animals in polluted areas. The present study revealed lead concentration exceeded the permissible limits established by WHO 37 . The present study's findings align with the previous study, which reported a higher Pb level in the industrial polluted areas than in non-polluted areas.…”
Section: Discussioncontrasting
confidence: 47%
“…Metal content in forage  conversion factor  food intake by sheep Average weight Food intake and average weight of sheep were 1.3 kg and 75 kg respectively (Chen et al 2021a(Chen et al , 2021bHussain et al 2021).…”
Section: Dim ¼mentioning
confidence: 99%
“…The accumulated micropollutant bought by wastewater can cause a toxicological impact [14], such as neurotoxicity [15], nephrotoxicity [16], carcinogenicity [7], hepatoxicity, immunology toxicity, cardiovascular  ISSN: Int J Public Health Sci, Vol. 12, No.…”
Section: Introductionmentioning
confidence: 99%